Analysis of Pro-Environmental Behavior in Fishermen Families at Muara Siberut, Mentawai Islands, Indonesia - Gusti, Aria; Afifah, Fitrahul; El-Khairah, Siti Mardhiah (International Journal of Medical Science and Clinical Research Studies, 2025)
This study analyzed pro-environmental behavior among fishermen families in Muara Siberut, Mentawai Islands, Indonesia, focusing on waste disposal practices, vector disease control, footwear habits, ventilation behaviors, and cleaning the yard. A survey was used, utilizing formal questionnaires and qualitative interviews to analyze environmental behaviors and their determinants. Findings reveal significant environmental challenges, with 31.6% of households disposing of waste in rivers or beaches, 93.9% reporting vector disease presence, and 50% resorting to waste burning. Although 63.3% consistently wear footwear, sanitation practices remain inconsistent. The study highlights the urgent need for improved waste management infrastructure, targeted educational interventions, and policy support to promote sustainability. In conclusion, addressing environmental issues in fishing communities requires a multi-faceted approach, integrating socio-cultural factors, infrastructure development, and public health strategies to foster long-term behavioral change and environmental sustainability.